2005
DOI: 10.1007/s00268-005-7877-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Evolution of Inflammatory Response in a Model of Suprarenal Aortic Cross‐clamping with and without Hemorrhagic Shock. Systemic and Local Reactions

Abstract: Surgery of the abdominal aorta generates a systemic inflammatory response (SIR), a source of operative morbidity-mortality. In the present work we attempted to evaluate the evolution of SIR in an experimental model that simulates elective and urgent surgery on the abdominal aorta. Fifteen mini-pigs divided into three groups were used. The animals were subjected to suprarenal aortic/iliac clamping and bypass with a Dacron-collagen prosthetic graft. Groups were as follows: (1) sham (only aortic dissection); (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Abdominal aortic aneurysm surgery induces a systemic inflammatory response (SIR) [9, 10]. Inflammatory status along with toxic metabolic waste products inflow to the vena cava inferior from ischemic lower extremities as well as oxidative stress associated with surgical trauma might contribute to AKI development following AAA surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal aortic aneurysm surgery induces a systemic inflammatory response (SIR) [9, 10]. Inflammatory status along with toxic metabolic waste products inflow to the vena cava inferior from ischemic lower extremities as well as oxidative stress associated with surgical trauma might contribute to AKI development following AAA surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The peak expression of sP-selectin during acute coronary syndromes only has a 2-hour delay in relation to its peak expression on platelets [2527]. But another experiment has shown that, following aorta surgery, serum levels of sVCAM-1 and sICAM-1 might remain unchanged despite a significant increase of their tissue counterparts in kidneys [9]. This indicates that the relationship between membrane-bound and soluble forms might be quite complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la actualidad se han descrito más de 20; detallaremos a continuación las más importantes relacionadas con el proceso inflamatorio en la reperfusión (182,259,264,184,40,132) .…”
Section: Citocinasunclassified